Fake News and Sarcasm, what is the limit of a critic and what is intentionally fake? - Cardoso Durier da Silva, Fernando; Bicharra Garcia, Ana Cristina (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2019: Anais do XV Simpósio Brasileiro de Sistemas ColaborativosDO - 10.5753/sbsc.2019.7807, 2019)
Nowadays it is hard to distinguish what is a fake information made to mislead, cause havoc and hysteria than a true critic that has only the intention to highlight a social problem or an abnormality of some sort. In order to diminish the number of false positives in fake news detection, we experimented two neural network models trained by a combined set of true, fake and sarcastic news in order to test how accurate would be our model. This paper has the goal to propose future steps of an ongoing experiment and discuss the usage of collaboration aided by machines to gather such data to the models.